Saundaryakaḷa : lalita kaḷala utpatti vikāsa tattvamulu - Vidyānandaṃ, Molatrāṭi (Si. El. Es. Telugu Pablikēṣans, 1978)
On aesthetic theories and their application to Indian art and Telugu poetry; a study.